Pattern and Appropriateness of Antimicrobial Prescriptions for Upper Respiratory Tract and Dental Infections in Male Prisoners in Italy - Gabriella Di Giuseppe; Raffaele Lanzano; Armando Silvestro; Francesco Napolitano; Maria Pavia (Antibiotics, 2021)
Background: This study explored the antimicrobial prescribing pattern for upper respiratory tract and dental infections in prisoners in Italy, with specific attention paid to the appropriateness of indication and its potential determinants. Methods: This investigation was conducted through the consultation of clinical records of adult male inmates in a prison in the south of Italy. Results: Prescription of antimicrobials for upper respiratory tract infections ranged from 41.9% in influenza diagnoses to 88% in pharyngitis diagnoses, with high prevalence also for bronchitis (73.5%) and common cold (57.7%), and those for dental infections ranged from 82% in pulp necrosis and symptomatic apical periodontitis/pulp necrosis and localized acute apical abscess diagnoses, to 85.7% in symptomatic irreversible pulpitis with or without symptomatic apical periodontitis diagnoses. The most frequently prescribed antimicrobial was amoxicillin and clavulanic acid (33.8%), followed by amoxicillin (26.5%), macrolides (19.8%) and third-generation cephalosporins (7.9%). The overall antimicrobial overprescription was 69.4%, whereas an antimicrobial prescription was provided in all 52 cases in which it was indicated. The inappropriate antimicrobial prescriptions were significantly less likely for bronchitis, influenza and symptomatic irreversible pulpitis with or without symptomatic apical periodontitis compared to common cold/pharyngitis/rhinosinusitis, and when the antimicrobial prescription was provided by medical specialists compared to prison physicians, whereas antimicrobial overprescriptions without indications were significantly more frequent in patients with underlying chronic clinical conditions. Conclusions: A concerning widespread practice of inappropriate antimicrobial prescriptions in prisoners was found. Diagnoses-specific monitoring of antimicrobial use and prison-focused antimicrobial stewardship policies are strongly needed.